A biological intelligent scheduling algorithm for scheduling with batch size and non-cutting time consideration. (29th December 2006) - Zhou, Yaqin; Li, Beizhi; Yang, Jianguo
Non-cutting time or auxiliary time may not be ignored in solving job shop scheduling problems, which includes the time for transportation or transferring of job pieces and for adjustment of cutting tools and fixtures, etc. while considering batch that can also reduce the number of transporting and adjusting times. In this paper, a complicated scheduling problem is studied, which fully considers batch size, the available time of jobs and non-cutting time as the necessary operating conditions based on practical production. Firstly, a model of this problem is given, along with a biological immune algorithm for solving it. Then the key techniques for realising the intelligent algorithm are introduced, including the design of antibody encoding, the computation and optimisation method of the starting time of each job, and the operation of crossover and mutation. Results from the trial solutions of the problem with considerations of non-cutting time, batch size and multiconstraints show that the biological intelligent scheduling algorithm proposed is effective in solving this kind of scheduling problem.